2019
DOI: 10.1103/physrevlett.123.265501
|View full text |Cite
|
Sign up to set email alerts
|

Local Density Fluctuation Governs the Divergence of Viscosity Underlying Elastic and Hydrodynamic Anomalies in a 2D Glass-Forming Liquid

Abstract: If a liquid is cooled rapidly to form a glass, its structural relaxation becomes retarded, producing a drastic increase in viscosity. In two dimensions, strong long-wavelength fluctuations persist, even at low temperature, making it difficult to evaluate the microscopic structural relaxation time. This Letter shows that, in a 2D glass-forming liquid, relative displacement between neighbor particles yields a relaxation time that grows in proportion to the viscosity. In addition to thermal elastic vibrations, hy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 48 publications
5
26
0
Order By: Relevance
“…3(c), we observe that, while the standard relaxation time decreases logarithmically with L, the CR one is L independent. These results closely parallel those observed in strictly two-dimensional systems [19][20][21][22][23][24][25] and demonstrate that LW fluctuations sensibly affect the structural relaxation dynamics of confined liquids.…”
Section: Confined Liquidssupporting
confidence: 83%
See 1 more Smart Citation
“…3(c), we observe that, while the standard relaxation time decreases logarithmically with L, the CR one is L independent. These results closely parallel those observed in strictly two-dimensional systems [19][20][21][22][23][24][25] and demonstrate that LW fluctuations sensibly affect the structural relaxation dynamics of confined liquids.…”
Section: Confined Liquidssupporting
confidence: 83%
“…The size dependence of the relaxation dynamics of confined liquids offers an alternative and unexplored approach to investigate the dimensionality crossover. Indeed, two-dimensional systems differ from their threedimensional counterpart because Mermin-Wagner [18] * massimo@ntu.edu.sg long-wavelength (LW) fluctuations make their relaxation dynamics size dependent [19][20][21][22][23][24][25]. This alternative approach is also convenient as Mermin-Wagner fluctuations are always present in two-dimensional systems; conversely, the two-and the three-dimensional phase behaviour do not qualitatively differ in all systems [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the lognonug allows studying numerically the long-wavelength regime q → 0. This could be particularly interesting to study the long-wavelength properties of the structural glass transition in two dimensions, a topic that is recently receiving increasing attention [76,77]. The proposed integration scheme resorts completely on trapezoidal integration in the case of hard spheres, while for hard disks we introduced a mix of trapezoidal and analytical integration that allows us to deal successfully with the singularities appearing in the MCT kernel for d = 2.…”
Section: Discussionmentioning
confidence: 99%
“…Using computer simulations, Flenner and Szamel showed that many typical features of glassy dynamics in 3D systems (e.g., the transient cage formation, the coupling between orientational and translational relaxations) are absent in 2D samples, indicating that the glass transitions in 2D and in 3D differ significantly [21]. However, later experiments [8,9] and simulations [22,23] have clearly demonstrated that this difference is induced by Mermin-Wagner fluctuations which refer to the phenomenon that particles in 2D can move significantly without obviously changing their local environments (neighbors). Once the influence of these long-length fluctuations has been removed by using cage-relative quantities, the 2D systems are found to display all typical features of glassy dynamics, just like their 3D counterparts [8,9,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…However, later experiments [8,9] and simulations [22,23] have clearly demonstrated that this difference is induced by Mermin-Wagner fluctuations which refer to the phenomenon that particles in 2D can move significantly without obviously changing their local environments (neighbors). Once the influence of these long-length fluctuations has been removed by using cage-relative quantities, the 2D systems are found to display all typical features of glassy dynamics, just like their 3D counterparts [8,9,22,23]. Hence this issue is resolved and 2D colloidal suspensions can be used as valuable models of glass-forming systems [24].…”
Section: Introductionmentioning
confidence: 99%